EXPLORING THE 360-DEGREE ASSESSMENT FRAMEWORK: IMPLICATIONS OF NEP-2020 FOR HOLISTIC EDUCATION IN INDIA - J. Antoni Santha Seelan 1, Dr. KVSN Murty 2, T Arun Christopher 3, C Brintha 4 , (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
India being a traditional seat of learning has greatly contributed to the growth and development of human civilization. In the 21st century there has been a phenomenal growth in every sector and industries and influencing the system of education. To make education more dynamic and pragmatic, NEP-2020 has proposed principle changes in the system of education and assessment. 360-degree assessment in principle is the comprehensive process of assessing the child’s all round development and promotes better learning. This article will through light on the major aspect of NEP-2020 in the light of assessment, by elaborating the concept, significance, and challenges of implementing 360 degree as an assessment mechanism in education system of India.